2014
DOI: 10.1126/scitranslmed.3008793
|View full text |Cite
|
Sign up to set email alerts
|

HCV-Induced Immune Responses Influence the Development of Operational Tolerance After Liver Transplantation in Humans

Abstract: Pathogen-induced immune responses prevent the establishment of transplantation tolerance in experimental animal models. Whether this occurs in humans as well remains unclear. The development of operational tolerance in liver transplant recipients with chronic hepatitis C virus (HCV) infection allows us to address this question. We conducted a clinical trial of immunosuppression withdrawal in HCV-infected adult liver recipients to elucidate (i) the mechanisms through which allograft tolerance can be established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 48 publications
4
91
0
Order By: Relevance
“…A similar mechanism may be driven by CMV infection after LTx, which also causes inflammation in the graft and in other organs (52), whereas CMV is able to induce IFN-a production (56). A possible relationship between inflammation and reduced alloresponses after LTx is supported by a recent study that showed that chronic HCV patients who are operationally tolerant after LTx overexpress type I IFN and IFN-stimulated genes in the liver graft (57). A second possible explanation for the association between CMV infection and CD8 + T cell hyporesponsiveness is that CMV produces viral IL-10 (58), which inhibits the expansion of alloreactive CD8 + T cells.…”
Section: Discussionmentioning
confidence: 60%
“…A similar mechanism may be driven by CMV infection after LTx, which also causes inflammation in the graft and in other organs (52), whereas CMV is able to induce IFN-a production (56). A possible relationship between inflammation and reduced alloresponses after LTx is supported by a recent study that showed that chronic HCV patients who are operationally tolerant after LTx overexpress type I IFN and IFN-stimulated genes in the liver graft (57). A second possible explanation for the association between CMV infection and CD8 + T cell hyporesponsiveness is that CMV produces viral IL-10 (58), which inhibits the expansion of alloreactive CD8 + T cells.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, HCV infection does not negatively influence the establishment of operational tolerance of the liver allograft after the withdrawal of immunosuppression, whereas concomitant infections are generally considered to be detrimental to the process of allograft tolerance [62]. As expected, the induction of Treg might be involved in this phenomenon, alongside high levels of intrahepatic interferon-stimulated gene expression which may paradoxically promote a tolerogenic micro-environment in the context of HCV infection.…”
Section: Open Issues and Future Perspectivesmentioning
confidence: 81%
“…18,19 Based on these experimental observations, Alberto Sanchez-Fueyo and co-workers (London, UK) have demonstrated that persistent hepatitis C virus (HCV) infections exert clinical immunoregulatory effects that alleviate deleterious alloimmune responses. 20 This original work challenges the notion that heterologous immunity and inflammatory responses within the transplant will necessarily prevent tolerance.…”
Section: Deciphering Anti-infectious Immune Responses and Pathogen-inmentioning
confidence: 96%